On The Third Type of Headed Relative Clause in Post‐Classical and Early Byzantine Greek. (31st August 2018) - Bentein, Klaas; Bağrıaçık, Metİn
Abstract: It has been claimed that Archaic and Classical Greek had two main types of headed relative clauses: (i) postnominal externally headed relative clauses; and (ii) internally headed relative clauses (Perna2013a ;2013b ; Fauconnier2014 ; Probert2015 ). In this article, we take a closer look at the semantic and syntactic properties of the second category in Post‐classical and Early Byzantine Greek (I–VIIIad ). Analysing a corpus of documentary texts, we show that a good deal of the examples in this period do not correspond to the established properties of internally headed relative clauses in the history of Greek. This leads us to propose that at least some examples that are apparently internally headed should be revised as a third relative clause type, namely prenominal externally headed relative clauses. We hypothesise that such examples came into existence through form‐function reanalysis of internally headed relative clauses, a process which we suggest took place already in the Classical period (V–IVbc ). In the last part of our article, we investigate the motivation for the choice of internally headed and prenominal externally headed relative clauses over the postnominal ones: we show that such examples occur strikingly frequently in formal texts such as contracts, petitions and formal letters. We propose that in such texts, internally headed and prenominal externally headed relative clauses, which are syntactically more complex, function as 'transparent signifiers' (Hodge & Kress1988 ), serving as a marker of a higher social level.